INVESTIGATION OF PHYTOPLANKTON COMMUNITY IN “YEREVANYAN LICH” RESERVOIR AND THE HRAZDAN RIVER IN THE CONDITIONS OF ALGAL BLOOM (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
Phytoplankton quantitative and qualitative parameters in “Yerevanyan Lich” Reservoir and the Hrazdan River were investigated in April and June–August 2015. The results of the study showed that algal bloom registered in “Yerevanyan Lich” Reservoir in summer 2015 created new environmental conditions which led to significant changes in reservoir’s phytoplankton dominant complex, affecting also phytoplankton composition in the Hrazdan River sites located downstream from the reservoir.
Keywords: “Yerevanyan Lich” Reservoir, Hrazdan River, phytoplankton, algal bloom, impacts